Tau Protein Modulates Perineuronal Extracellular Matrix Expression in the TauP301L-acan Mouse Model - Sophie Schmidt (Biomolecules, 2022)
Tau mutations promote the formation of tau oligomers and filaments, which are neuropathological signs of several tau-associated dementias. Types of neurons in the CNS are spared of tau pathology and are surrounded by a specialized form of extracellular matrix; called perineuronal nets (PNs). Aggrecan, the major PN proteoglycans, is suggested to mediate PNs neuroprotective function by forming an external shield preventing the internalization of misfolded tau. We recently demonstrated a correlation between aggrecan amount and the expression and phosphorylation of tau in a TauP310L-acan mouse model, generated by crossbreeding heterozygous aggrecan mice with a significant reduction of aggrecan and homozygous TauP301L mice. Neurodegenerative processes have been associated with changes of PN structure and protein signature. In this study, we hypothesized that the structure and protein expression of PNs in this TauP310L-acan mouse is regulated by tau. Immunohistochemical and biochemical analyses demonstrate that protein levels of PN components differ between TauP301LHET-acanWT and TauP301LHET-acanHET mice, accompanied by changes in the expression of protein phosphatase 2 A. In addition, tau can modulate PN components such as brevican. Co-immunoprecipitation experiments revealed a physical connection between PN components and tau. These data demonstrate a complex, mutual interrelation of tau and the proteoglycans of the PN.